IPP AS PREDICTIVE FACTOR FOR ACUTE URINARY RETENTION IN BPH PATIENTS - Budaya, Taufiq Nur; Purnomo, Basuki B.; Daryanto, Besut; Seputra, Kurnia Penta; Satyagraha, Paksi (Indonesian Urological Association, 2014)
Objective: To demonstrate usefulness of Intra Prostatic Protrusion (IPP) as Predictive Factor for Acute Urinary Retention (AUR) in Benign Prostate Hyperplasia (BPH) Patients. Material & methods: Cross sectional retrospective study of case records from January to July 2012 of BPH patients at Saiful Anwar General Hospital (SAGH) Malang was carried out. The data were collected from the Medical Record Division in SAGH Malang. We noted age, prostate volume, IPP, IPSS and urinary retention status. The patients were classified by IPP degree < 5 mm (group A), 5-10 mm (group B), 10 -15mm (group C), > 15mm (group D) and we compared all parameters that we noticed. Results: Eighty patients, mean age was 66.32 years were enrolled. Transabdominal ultrasound determined the mean IPP was 13.5 mm, and prostatic volume 95 cc. IPP values were distributed as follows: group A 10 (12.5%), group B 25 (31.25%), group C 24 (30%), group D 21 (26.25%), with AUR incidence in group A 20%, group B 36%, group C 79%, and group D 81%. The IPP showed a significant correlation with urinary retention (r = 0.8, p < 0.05, OR = 15) and IPSS (r = 0.6, p < 0.05). Conclusion: IPP can be used as predictive factor for the incidence of acute urinary retention in BPH Patients.Keywords: Intra Prostatic Protrusion, Acute Urinary Retention, Benign Prostate Hyperplasia.